Preterm birth and exercise capacity: what do we currently know? - O’Dea, Christopher A.; Beaven, Michael L.; Wilson, Andrew C.; Smith, Elizabeth F.; Maiorana, Andrew; Simpson, Shannon J. (Frontiers in Pediatrics, 2023)
Abstract: Objectives: The long-term cardiopulmonary outcomes following preterm birth during the surfactant era remain unclear. Respiratory symptoms, particularly exertional symptoms, are common in preterm children. Therefore, cardiopulmonary exercise testing may provide insights into the pathophysiology. This review aims to outline the current knowledge of cardiopulmonary exercise testing in the assessment of children born preterm in the surfactant era. Design: A narrative literature review Methods: Published manuscripts concerning the assessment of pulmonary outcomes using cardiopulmonary exercise testing in preterm children (aged <18y) were reviewed. Search terms related to preterm birth, bronchopulmonary dysplasia and exercise were entered into electronic databases including Medline, Pubmed, and Google Scholar. Reference lists from included studies were scanned for additional manuscripts. Results: Preterm children have disrupted lung development with significant structural and functional lung disease and increased respiratory symptoms. The association between these (resting) assessments of respiratory health and exercise capacity are unclear, however expiratory flow limitation and an altered ventilatory response (rapid, shallow breathing) are seen during exercise. Due to the heterogeneity of participants, treatments and exercise protocols, the effect of the aforementioned limitations on exercise capacity in children born preterm is conflicting and poorly understood. Conclusion: Risk factors for reduced exercise capacity in those born preterm remain poorly understood, however, utilising cardiopulmonary exercise testing to its full potential the pathophysiology of exercise limitation in survivors of preterm birth will enhance our understanding of the role exercise may play. The role of exercise interventions in mitigating against the risk of chronic disease and premature death following preterm birth has yet to be fully realised and should be a focus of future robust randomised controlled trials.